The Transition from Welfare to Work and the Role of Potential Labor Income - Hilmar Schneider; Arne Uhlendorff (Institute for the Study of Labor (IZA), 2004)
It is often argued that the high level of welfare claims in Germany causes little incentive for workers with low productivity to seek for a job. We examine the influence of the ratio between estimated potential labor income and the welfare payment level on the probability of leaving social welfare. Using the GSOEP, we estimate a discrete time hazard rate model with competing risks and unobserved heterogeneity. Our results show that the ratio has a positive effect on the probability of leaving social welfare. This effect is especially relevant for households with a potential labor income higher than their welfare payment level.
Keywords: C41; J64; I38; 330; social welfare; labor supply; duration analysis; Sozialhilfe; Erwerbstätigkeit; Ökonomischer Anreiz; Arbeitsangebot; Deutschland